(untitled) (TAJ: Journal of Teachers Association, 2009)
The interferons (IFNs) are group of naturally occurring cytokines that are secreted by cells of mammalian immune system when they are stimulated by viral, bacterial and other antigens. There are number of alpha IFNs available for treatment purposes. The two most commonly used α-2a and α-2b are made by recombinant technology. When interferon Alpha-2a is combined with polyethylene glycol (PEG), it is known as pegylated interferon or PEG interferon. Polyethylene glycol (PEG) is a safe, inert and nontoxic molecule. Therapeutic benefits of altering proteins with PEG include an improvement in half-life due to reduced renal and cellular clearance, enhanced protection from proteolysis and a reduction in toxicity. doi: 10.3329/taj.v17i2.3460 TAJ 2004; 17(2): 113-116